ANALISIS PENGARUH QUALITY DIMENSION PADA KOMUNITAS ONLINE TERHADAP PURCHASE INTENTION - Christiarini, Renny; Wilhelmina, Wilhelmina (Universitas Indo Global Mandiri Palembang, 2021)
The emerging online community provides opportunities for consumers to participate in discussions whose purpose is to provide information to each other and influence fellow consumers regarding product information.The purpose of this research is to find out whether the dimensions of quality in online communities, namely the quality of relationships and the quality of information affect purchase intentions through reducing uncertainty with the moderating variable of involvement. The object of this research is the influence of online community quality dimensions on the purchase intention of smartphone products. Partial least square method is a method used to process this research data.The results of this study are information quality variables and relationship quality variables have significant influence on reducing uncertainty. Relationship quality and information quality significantly influence the purchase intention variable. The variable of uncertainty reduction influences and is significant on the purchase intention variable. There is significant moderation effect on the involvement variable on the uncertainty reduction variable on the purchase intention variable. In addition, the results of this study indicate the quality dimensions of online communities influence purchase intentions. The existence of quality information and good quality relationships in online communities will result in uncertainty reduction by visitors so that it will lead to product purchase intentions.